Pelatihan Entrepreneur Untuk Masyarakat Di Desa Wisata Boddia, Kecamatan Galesong, Kab. Takalar - Ab., Ahmad (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Entrepreneur Training for Communities in Boddia Tourism Village, Galesong District, Takalar Regency. The purpose of this community service activity is to increase community knowledge and skills about handicrafts and entrepreneurial products that can be sold as souvenirs and become an attraction in tourist villages. This training is aimed at housewives and women in Boddia Tourism Village. The method used in this training was presentation and hands-on practice. One of the handicrafts trained in this activity is knitting. The positive impact of this community service activity is that housewives can fill their spare time by knitting and utilizing used goods into a craft. This is because knitting is one of the drivers of the creative economy which can certainly increase community income. The results of the activity showed that the participants were very satisfied with this training activity, including the service of the activity committee, the quality of the training material provided, the ability of the trainer in providing material, the suitability of the material provided to the needs of the trainees, and the participants' satisfaction with the implementation of handicraft training.